PERBANDINGAN PERFORMANSI BILAH TAPPERLESS MENGGUNAKAN AIRFOIL CR001SM DAN PSU 94-097 PADA TURBIN ANGIN SUMBU HORIZONTAL SKALA KECIL - Akbar Dilla Shanca (2021)
Indonesia is a country that has abundant natural resources potential including geothermal, water, air, and sea waves. These natural resources can be converted into electrical energy which can later be consumed by the community. One of the energy sources that can be used is wind. Wind energy is easy to obtain, especially in the location of the ocean and land. Wind energy is used to turn the generator at the Wind Power Plant so that it can produce electrical energy. One of the important components in a wind turbine is the blade. The blade structure has Coefficient Lift and Coefficient Drag values which are influenced by the shape of the airfoil. This study discusses the design of tapperless blades using CR001SM and PSU94-097 airfoils. The blade is designed using dimensions of 800 mm x 120 mm x 30 mm where the CR001SM airfoil has a twist range of 11,581° to 7,729°, and the PSU94-097 airfoil from base to tip is 11.34° to 7,377°. After the design is complete, it is necessary to perform a simulation using the QBlade software. The results of the simulation show that the blade using the CR001SM airfoil has an efficiency of 45.569% at TSR 5, and the PSU94-097 airfoil has an efficiency of 45.307%. Field testing was carried out on the coast of Ciheras, Tasikmalaya for 5 days. The test results show that the actual power gain on the blade using the CR001SM airfoil has a maximum power of 343.19 Watt with the total electrical energy obtained being 3,199.98 Wh. The blade with airfoil PSU94-097 has a maximum actual power of 266.26 Watt with the total electrical energy obtained being 2,441.85 Wh. Therefore the CR001SM airfoil has a higher power gain rate than the PSU94-097.